The Greeks Dictionary of the Systematic Dialogue: A Statistical Survey - Abdolbaset Arab Yousofabadi; - -; - - (پژوهش نامه معارف قرآنی, 2018)
Any text can play a significant role in reproduction of its specific ideology provided that it can gain access to those discourses that make social actors involved in hegemony. Van Leeuwen’s (2008) discourse-oriented theory is one of the approaches to discourse analysis that aims at unraveling the hidden layers of language in written and oral texts by drawing on socio-semantic factors and with a focus on social actors. This approach to discourse analysis can have a special position is Quranic studies since discoursal structures of Quran and their mysterious features indicate that the hidden ideology behind them are more or less the same. Drawing on analytical-descriptive method, and Van Leeuwen’s (2008) discourse-oriented model, the present study aims at examining the discourse of Al-Jinn (English equivalent of “Goblin”) Sureh. This Sureh was selected because it involves various social actors and speech acts by narrating a group of Goblins. The results of the study indicated that discoursal elements related to candidness in comparison to those of secrecy were more frequent (with the frequencies of 172 and 24 respectively). This finding suggests that using a stylish creativity and innovation, this Sureh has attempted to familiarize the audience with persons, groups, places, and times in which the social actors have an active role. Besides, specificity of allusion type (with the frequency of 63), role specificity method (with frequency of 60), and nature specificity (with the frequency of 49) had the highest representations among the social actors’ statements and remarks.